DEFORMATION PATTERN IN THE WESTERN NORTH AEGEAN TROUGH: PRELIMINARY RESULTS - Sakellariou, D.; Rousakis, G.; Vougioukalakis, G.; Ioakim, Ch.; Panagiotopoulos, I.; Morfis, I.; Zimianitis, E.; Athanasoulis, K.; Tsampouraki-Kraounaki, K.; Mpardis, D. (Bulletin of the Geological Society of Greece, 2016)
Preliminary interpretation of swath bathymetry data and seismic profiles acquired during four cruises of "YPOTHER/Aegean Explorations" project aboard R/V Aegaeo provides insights into the fault network, fault kinematics and deformation pattern of the western part of the North Aegean Trough (NAT). The N40°E trending western part of the dextral North Anatolian Fault (NAF) runs along the southern margin of the NAT. Numerous high-angle fault splays initiate from and at low angle to NAF. They run firstly in NE-SW direction and then gradually turn to SE-NW forming an imbricate fault pattern, a nicely developed horsetail structure at the western termination of the NAF. The horsetail pattern deforms the NAT’s sedimentary infill forming elongate, curved, uplifting or subsiding tectonic blocks arranged along the fault splays. Instead of the expected transtension, the Western NAT’s infill displays dextral shearing and transpression associated with a major stress axis in NW-SE direction. The possible explanation for the transpressional deformation of the Western NAT infill may be related with the change of the trend of NAF from N40°E in the western trough to N70°E east of Lemnos Island.